Peran Penilai Pemerintah Dalam Rangka Pengelolaan Barang Milik Negara Berupa Aset Tetap - Nurbiyanto Nurbiyanto (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2022)
State-Owned Property (SOP) in the form of fixed assets were so large in quantity and values. In managing SOP, a SOP appraisal process is needed so it can certain the value. This study wants to reveal the role of appraisers in the management of SOP, especially fixed assets. The study uses literature studies to explore the role of Government Appraisers in the management of SOP. Literature from valuation theory is used to answer the urgency of appraisers in asset transactions. Regulatory literature to answer the SOP management process requires an appraisal. Based on the results of the analysis of property valuation theory, SOP valuation is necessary due to nature, and characteristics of SOP are goods for which the level of price information is low or difficult to obtain, so Government Appraiser assistance is needed to provide an estimated value. Based on the results of the regulatory analysis, it was found that there are three main roles for the Government Appraiser in the management of SOP, namely for recording financial reports in the balance sheet, transfer, and utilization of SOP. The role of the Government Appraiser is to provide fair value information to the manager or user of the goods to make decisions regarding SOP management. Keywords: Appraisal, Government Appraiser, State-Owned Property